Analysis of curved thin wires radiating over a layered medium and some engineering applications. Issue 6 (13th April 2021) - Poljak, D.; Doric, V.; Birkic, M.
Abstract : The paper deals with modelling of radiation from arbitrarily shaped thin wires above a multilayer and related engineering applications. The formulation is based on the set of corresponding Pocklington integro-differential equations (IDEs) for curved wires. The influence of lower layered half-space is taken into account by means of simplified reflection coefficient stemming from modified image theory (MIT). The set of coupled IDEs is handled via Galerkin Bubnov variant of indirect boundary element method (GB-IBEM) for curvilinear elements. The related field radiated from a wire configuration is obtained from corresponding integral expressions including integration of the currents along a given wire configuration. Some illustrative computational examples for certain wire configurations pertaining to dipole antennas, power communication systems (PLC) and instrumental landing systems (ILS) are given in the paper.